2017
DOI: 10.1016/j.redox.2017.02.019
|View full text |Cite|
|
Sign up to set email alerts
|

CO-releasing molecules CORM2 attenuates angiotensin II-induced human aortic smooth muscle cell migration through inhibition of ROS/IL-6 generation and matrix metalloproteinases-9 expression

Abstract: Ang II has been involved in the pathogenesis of cardiovascular diseases, and matrix metalloproteinase-9 (MMP-9) induced migration of human aortic smooth muscle cells (HASMCs) is the most common and basic pathological feature. Carbon monoxide (CO), a byproduct of heme breakdown by heme oxygenase, exerts anti-inflammatory effects in various tissues and organ systems. In the present study, we aimed to investigate the effects and underlying mechanisms of carbon monoxide releasing molecule-2 (CORM-2) on Ang II-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 72 publications
6
19
0
Order By: Relevance
“…These results are consistent with other studies on the role of CO donors in protecting against oxidative stress, i.e. studies of Tsai et al [ 8 ] demonstrated that CORM-2 inhibits angiotensin II-induced human aortic smooth muscle cells migration through inactivation of NADPH oxidase/reactive oxygen species generation. Babu et al [ 14 ] also noted that CORM-2 shows antioxidant property in murine intestinal epithelial MODE-K cells under oxidative stress (induced by H 2 0 2 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results are consistent with other studies on the role of CO donors in protecting against oxidative stress, i.e. studies of Tsai et al [ 8 ] demonstrated that CORM-2 inhibits angiotensin II-induced human aortic smooth muscle cells migration through inactivation of NADPH oxidase/reactive oxygen species generation. Babu et al [ 14 ] also noted that CORM-2 shows antioxidant property in murine intestinal epithelial MODE-K cells under oxidative stress (induced by H 2 0 2 ).…”
Section: Discussionsupporting
confidence: 92%
“…Babu et al [ 14 ] also noted that CORM-2 shows antioxidant property in murine intestinal epithelial MODE-K cells under oxidative stress (induced by H 2 0 2 ). Moreover, it is very important that our used concentrations of CORM-2 in our model in vitro are consistent with other studies [ 8 , 11 , 14 , 25 , 29 ], i.e. Tsai et al [ 8 ] observed that 50 μM CORM-2 has antioxidant activity.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Carbon monoxide-releasing molecules (CORMs), a group of compounds capable of carrying and liberating controlled quantities of CO, have shown promise for delivering exogenous CO without altering COHb to toxic levels [ 11 , 18 20 ]. Although the mechanisms by which CORM-derived CO might offer its beneficial effects have not yet been thoroughly investigated, many studies substantiate the protective role of CORM-derived CO against cellular and tissue damage in numerous models of injury, such as renal ischemia-reperfusion injury, hemorrhagic stroke, traumatic brain injury, transplantation, sepsis, hypertension, and cardiovascular disorders [ 21 – 28 ].…”
Section: Introductionmentioning
confidence: 99%